A (in)suficiência da legislação ambiental para preservação e conservação da Mata Atlântica em Sergipe - Santos, Robéria Silva (2022)
Deforestation in the Atlantic Forest increased after two consecutive periods of decline, as a total of 14,502 ha were deforested between 2018-2019, an increase of 27.2% compared to the previous period (2017-2018), which was 11,399 hectares , according to data from the Atlantic Forest Atlas and the National Institute for Space Research (INPE). Specifically in Sergipe, 98 hectares were deforested between 2018-2019, and between 2019-2020 it increased to 138 hectares according to the non-governmental organization SOS MATA ATLÂNTICA. While the legal system, in addition to specific provisions, also has laws of general scope within the scope of environmental legislation and punitive laws, as well as CONAMA resolutions. This work has the general objective of evaluating deforestation in terms of the quantity of the deforested area of the Atlantic Forest of Sergipe in view of the entry into force of each legislation since 1985, which aims to protect it directly and indirectly. The hypothesis, within what the hypothetical deductive approach method proposes, is the (in)sufficiency of environmental legislation in the preservation and conservation of the Atlantic Forest in Sergipe in the period from 1985 to 2019. For the purposes of developing this study, the methodology used to be applied in terms of means initially, the georeferenced database will be used, composed of vector and matrix (raster) formats; the vector files of the Atlantic Forest biome acquired from the Ministry of the Environment (MMA), and from the Special State Secretariat for Urban Development and Sustainability (SEDURBS), and the territorial limits of the states and municipalities of Brazil obtained from the Brazilian Institute of Geography and Statistics (IBGE). the matrix files will be the land use and cover since 1985, to be acquired from the Mapbiomas project version 5.0, prepared for the Atlantic Forest biome, whose MapBiomas classification is generated based on annual maps of land use and cover, from an automatic classification routine with the use of Randon Forest type decision tree algorithms (random forest) available on the Google Earth Engine (GEE) platform, as well as a bibliographic search of environmental legislation that directly or indirectly provides for the preservation and conservation of the Atlantic Forest in Sergipe, books, scientific publications and periodicals within the scope of the proposal. In the period from 1985 to 2019, the Atlantic Forest of Sergipe showed a significant increase in anthropic uses and land cover (pasture, agriculture and pasture mosaic and infrastructure) and a reduction in natural forest and nonforest ecosystems. Despite a series of laws that protect natural forest and non-forest ecosystems in the Atlantic Forest of Sergipe, it is observed that in the analyzed period (1985 to 2019) there was deforestation and anthropization of these ecosystems. Thus, it is concluded that environmental and forestry legislation is insufficient for the protection of the Atlantic Forest of Sergipe, which uses command and control mechanisms.